2022
DOI: 10.1021/acs.accounts.1c00753
|View full text |Cite
|
Sign up to set email alerts
|

Metalloporphyrins as Catalytic Models for Studying Hydrogen and Oxygen Evolution and Oxygen Reduction Reactions

Abstract: Metrics & More Article Recommendations * sı Supporting Information CONSPECTUS: The hydrogen evolution reaction (HER), oxygen evolution reaction (OER), and oxygen reduction reaction (ORR) are involved in biological and artificial energy conversions. H−H and O−O bond formation/cleavage are essential steps in these reactions. In nature, intermediates involved in the H−H and O−O bond formation/cleavage are highly reactive and short-lived, making their identification and investigation difficult. In artificial catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
122
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 192 publications
(130 citation statements)
references
References 73 publications
0
122
0
Order By: Relevance
“…Therefore, the identification of new cathode catalysts that are inexpensive, methanol resistant and easy to prepare as replacements for Pt‐based materials is a crucial task related to fuel cell development. Good progress has been made in the study of the ORR mechanism by porphyrins and their derivative bioenzyme catalysts, as reported by Cao and his colleagues [5–7] . Carbon‐based monoatomic metal cathode catalysts are an excellent alternative to Pt‐based catalyst materials because they are less expensive, resistant to methanol, stable and can be produced on a large scale [8,9] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the identification of new cathode catalysts that are inexpensive, methanol resistant and easy to prepare as replacements for Pt‐based materials is a crucial task related to fuel cell development. Good progress has been made in the study of the ORR mechanism by porphyrins and their derivative bioenzyme catalysts, as reported by Cao and his colleagues [5–7] . Carbon‐based monoatomic metal cathode catalysts are an excellent alternative to Pt‐based catalyst materials because they are less expensive, resistant to methanol, stable and can be produced on a large scale [8,9] .…”
Section: Introductionmentioning
confidence: 99%
“…Good progress has been made in the study of the ORR mechanism by porphyrins and their derivative bioenzyme catalysts, as reported by Cao and his colleagues. [5][6][7] Carbonbased monoatomic metal cathode catalysts are an excellent alternative to Pt-based catalyst materials because they are less expensive, resistant to methanol, stable and can be produced on a large scale. [8,9] Many current studies on transition metal single-atom catalysts, such as the single-atom Cu-S 1 N 3 reported by Yu and his colleagues, have shown good catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the research on photocatalytic hydrogen evolution (PHE) has been developed very fast for the production of H 2 as a clean energy and renewable fuel that would reduce the consumption of fossil fuels and alleviate the global warming crisis. 6 To date, various photocatalysts based on transition metal complexes, [7][8][9][10][11][12] porous materials, 3,[13][14][15][16] metal suldes/ oxides, [17][18][19] organic and inorganic hybrids, 11,[20][21][22][23][24][25] organic molecules, [26][27][28][29] and porphyrins 5,[30][31][32][33][34][35][36] have been demonstrated for efficient PHE. Among them porphyrins received much more attention for PHE due to their strong light absorption in the UVvisible region and easily tailorable photophysical and redox properties by integrating different aromatic chromophores to the porphyrin ring and inserting different metals in the porphyrin ring.…”
Section: Introductionmentioning
confidence: 99%
“… As such, a protonated 2-pyridyl substituent at the Co porphyrin core improves the formal selectivity to 4e – reduction to 70% compared to 30% for tetraphenylporphyrin (CoTPP) in the 1 M H 2 SO 4 electrolyte at an overpotential of 830 mV . Similarly, an atropoisomer bearing four amido groups favoring the stabilization of the O 2 adduct via hydrogen bonding was also demonstrated to give an electron transfer number (ETN) of 3.75 in the alkaline electrolyte. , An alternative approach utilizes inter- or intramolecular binding of two metal atoms to the O 2 molecule with the formation of a μ-superoxo intermediate [Co–O–O–Co], which facilitates the cleavage of the O–O fragment. , The intramolecular binding could be illustrated on the example of Co porphyrin-porphyrin dyad, which places Co atoms close enough for the 4e – mechanism to become dominant (selectivity to H 2 O ≈ 95% at η = 510 mV, electrolyte 0.5 M H 2 SO 4 ) . In turn, the involvement of intermolecular binding is possible only for small, sterically unloaded molecules such as unsubstituted Co porphyrin (Figure S1b) which shows selectivity to 4e – reduction of more than 90% at 0.77 V vs NHE .…”
Section: Introductionmentioning
confidence: 99%